2018
DOI: 10.17265/2328-2150/2018.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Anemia as a Predictor of Mortality in Patients with Decompensated Heart Failure

Abstract: Objective: To correlate the presence of anemia with mortality in hospitalized patients with decompensated HF (heart failure). Methods: A total of 148 patients hospitalized for HF compensation were analyzed from April 1 to December 31, 2017 in a tertiary referral hospital for cardiovascular diseases. The diagnosis of anemia was established according to the Brazilian Ministry of Health criteria, considering a serum hemoglobin value of < 13 g/dL for men and < 12 g/dL for women. Data were collected through medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Anemia is present in more than half of HF patients, especially if there is renal insufficiency, and this is in relation to the degree of both kidney and HF. The role of anemia in the literature is variable; it appears as an intermediate variable not systematically associated with a long-term prognosis in the evidence reported by other authors [ 23 , 24 , 25 , 26 , 27 ], although certain population registries have associated low levels of hemoglobin with a poorer long-term prognosis [ 25 ]. Our results support anemia as more of a marker associated with gender, renal insufficiency and probably poorer clinical conditions than as a variable directly associated with mortality, in agreement with what other authors have suggested [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anemia is present in more than half of HF patients, especially if there is renal insufficiency, and this is in relation to the degree of both kidney and HF. The role of anemia in the literature is variable; it appears as an intermediate variable not systematically associated with a long-term prognosis in the evidence reported by other authors [ 23 , 24 , 25 , 26 , 27 ], although certain population registries have associated low levels of hemoglobin with a poorer long-term prognosis [ 25 ]. Our results support anemia as more of a marker associated with gender, renal insufficiency and probably poorer clinical conditions than as a variable directly associated with mortality, in agreement with what other authors have suggested [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%